(untitled) (AMJ (Advanced Medical Journal), 2023)
Background and Objective: Preterm labor is a significant reason for perinatal mortality and morbidity. This study was conducted to determine the effect of two regimens of progesterone to avoid preterm labor and the adverse perinatal outcomes in the two groups. Methods: A prospective clinical trial was performed in Maternity Teaching Hospital and Hawler Private Hospital in Erbil city, Kurdistan region, Iraq over a one-year period from 1 May 2019 until 1 May 2020. The study sample was 200 pregnant women with a short cervix and a risk of preterm birth; the sample was divided into two groups. Group I of 100 pregnant women received 400 mg progesterone vaginally once daily, and group II of 100 pregnant women received it twice daily, started from 16 weeks of gestation up to the time of delivery in both groups. Results: The rate of term pregnancy (? 37 weeks) was 87% among women in group II and 55% in women in group I. Accordingly, the rate of neonatal intensive care admission was significantly higher in group I than in group II (30% and 11%, respectively). The rate of respiratory distress syndrome was also significantly higher in group I (31%) than in group II (7%). Conclusion: The administration of progesterone 400 mg vaginally twice a day appears to be more effective than progesterone 400 mg vaginally once a day in preventing preterm birth and reducing the risk of adverse neonatal complications.